Improving Financial Planning Literacy and Investment Education for Teenagers in Dukuh Gamblok, Galangpengampon Village, Wonopringgo Subdistrict, Pekalongan Regency - Maulid, Rifqi; Isna, Khomsatul; Risqiyana, Kholishotur; Nabila, Fatin; Ayuanda, Leila Nisya; Aisyah, Dewi Risqi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Low levels of education and limited access to information in Gamblok Hamlet, Galangpengampon Village, Wonopringgo District, Pekalongan Regency, are the main factors contributing to poor financial literacy among adolescents. Most adolescents in this area have completed only elementary or junior high school, so they lack an adequate understanding of the importance of financial planning and personal finance management. As a result, they are prone to consumer behavior, lack savings habits, and lack an understanding of the risks and benefits of investing. This community service activity aims to improve adolescent financial literacy by providing education tailored to participants' understanding levels. The implementation method includes interactive outreach involving discussions, simple budgeting simulations, educational games, and an introduction to basic, easy-to-understand investment instruments, such as savings and gold. The activity results showed a significant increase in participants' understanding of money management, the importance of distinguishing between needs and wants, and awareness of saving and of safe investments. This education not only provides knowledge but also encourages changes in behavior toward wiser personal financial management. This activity is expected to be the first step toward forming healthy financial habits, increasing economic independence, and paving the way for the socio-economic development of the younger generation in rural areas with limited access to education.